2021
DOI: 10.3389/fonc.2021.781386
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR Polymorphism Is Associated With Severe Methotrexate-Induced Toxicity in Osteosarcoma Treatment

Abstract: BackgroundPrevious studies have revealed the critical role of methylene tetrahydrofolate reductase (MTHFR) polymorphisms in response to high-dose methotrexate (MTX)-induced toxicity in osteosarcoma patients. However, the conclusions remain controversial. In this setting, we performed a meta-analysis to determine their association more precisely.MethodEligible studies were searched and screened in PubMed, Web of Science, Cochrane Library, Clinical-Trials.gov, Embase, and China National Knowledge Infrastructure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In a meta-analysis by Zhu et al that included 14 studies with a sample size of 1714 children, the C677T mutant gene was significantly associated with hepatotoxicity ( 28 ). Additionally, several reports have confirmed a significantly higher risk of hepatic impairment in patients with mutant genotypes ( 29 - 32 ). El-Khodary et al also demonstrated significantly higher serum glutaminase levels in children with ALL who have CT and TT mutation compared to those with wild-type CC ( 33 ).…”
Section: Discussionmentioning
confidence: 92%
“…In a meta-analysis by Zhu et al that included 14 studies with a sample size of 1714 children, the C677T mutant gene was significantly associated with hepatotoxicity ( 28 ). Additionally, several reports have confirmed a significantly higher risk of hepatic impairment in patients with mutant genotypes ( 29 - 32 ). El-Khodary et al also demonstrated significantly higher serum glutaminase levels in children with ALL who have CT and TT mutation compared to those with wild-type CC ( 33 ).…”
Section: Discussionmentioning
confidence: 92%
“…19 . Among them, genetic factors may be involved in the activities of MTX-associated enzymes, which may affect the metabolism and intracellular transport of the drug, thereby inducing the associated toxicity 20 . In the present study, the potential impact of MTX-related gene polymorphisms on MTX-related toxicity and clearance delay during HD-MTX treatment was analyzed in 189 Chinese children with ALL.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of osteosarcoma is bimodal with age, with an initial peak at 10–14 years of age, and a second peak after 60 years [ 99 ]. Primarily, osteosarcoma tends to occur in the metaphysis of the distal femur and proximal tibia [ 100 ], while metastasis is mainly detected in the lung [ 101 , 102 ]. With an annual incidence of approximately 3–4 patients per million, osteosarcoma is a relatively common malignant tumor in pediatric cancers, as well as one of the leading causes of cancer-related death in children and adolescents [ 103 , 104 ].…”
Section: Overview Of Pyroptosismentioning
confidence: 99%